The influence of service dog partnerships on perceived and objective sleep quality for military veterans with PTSD - Bristol, Stephanie; Leighton, Sarah C.; Schwichtenberg, A. J.; Campbell, Rebecca L.; Ashbeck, Erin L.; Taylor, Daniel J.; Bedrick, Edward J.; O'Haire, Marguerite E. (Frontiers in Sleep, 2024)
Introduction: Sleep disturbances, fear of sleep, and nightmares are among the most reported symptoms for military service members and veterans (henceforth “veterans”) with posttraumatic stress disorder (PTSD), potentially contributing to treatment resistance and heightened suicidality. Despite available evidence-based interventions, many veterans still report difficulties. The complementary intervention of a psychiatric service dog may contribute to improvements in sleep quality for veterans with PTSD. Methods: This preregistered, non-randomized clinical trial evaluated the association between service dog partnership and sleep from baseline to 3-month follow-up. Participants were N = 155 veterans with PTSD (81 in the service dog group and 74 waitlisted controls). Outcome measures included self-report surveys measuring PTSD severity (PTSD Checklist for DSM-5, PCL-5) sleep quality (Pittsburgh Sleep Quality Index, PSQI), sleep disturbance (PROMIS Sleep Disturbance), and fear of sleep (Fear of Sleep Inventory-Short Form, FoSI-SF); morning sleep diaries measuring nightmares; and wrist-worn actigraphy. Regression models and mediation analyses were performed. Results: Service dog partnership was significantly associated with better subjective sleep (PSQI: mean difference -2.2, 95% CI [-3.4, -1.1], p < .001; PROMIS Sleep Disturbance: -3.6, 95% CI [-6.3, -0.9], p = .004; FoSI-SF: -6.6, 95% CI [-9.7, -3.5], p < .001) and odds of nightmares (OR = 0.45, 95% CI [0.26, 0.76], p =.003). Service dog partnership was not associated with a change in actigraphy-based measures of sleep (sleep onset: -4.5, 95% CI [-12.2, 3.2]; sleep duration: -4.7, 95% CI [-25.9, 16.6]; wake after sleep onset: 6.0, 95% CI [-2.1,14.1]; sleep efficiency: -0.4, 95% CI [-3.4, 2.5]). The estimated proportion of the effect of service dogs on PTSD severity mediated by fear of sleep was 0.26 (95% CI [0.10, 0.48]). Discussion: Compared to the control group, veterans with service dogs for PTSD reported better sleep quality, less sleep disturbance, and less fear of sleep after three months. However, service dog partnership was not associated with differences in actigraphy-measured sleep. These findings may support psychiatric service dog partnership as a supplemental intervention for veterans with PTSD.